How hot is too hot - Cotter, J. (FINA World Sports Medicine Congress, 18, 2016)
Prof Jim Cotter, Otago University (NZL), and Dr. Carl Bradford, Otago University (NZL), discuss the topic "How Hot is Too Hot? Open Water Swimming in Warm Temperatures" at the FINA World Sports Medicine Congress 2016 (27:03 min).